Relationship between Family Support and Self-Care in Hypertension Patients - Vincencius Surani; Lilik Pranata; Teresia Erina Sestiyowati; Dini Anggraini; Sindi Ernawati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Hypertension is a health problem characterized by an increase in blood pressure above 140/90 mmHg. Hypertension can cause serious medical problems such as problems with the heart, brain and kidneys and can even cause death. The purpose of this study was to analyze the relationship between family support and self-care in hypertension sufferers. This research is a quantitative research with a correlational descriptive design using a cross-sectional approach. Based on inclusion and exclusion criteria, the number of respondents in this study was 40 respondents. The data collection tool uses a questionnaire which consists of a demographic survey of respondents, family support and self-care. Research data were analyzed using Kendall's tau-b statistical test. The results showed that there was no significant relationship between family support and self-care in hypertension sufferers. Self-care plays an important role in people with hypertension.